Communication culture as a defense system in the midst of crises - Zahia Abaz (International Journal of Social Communication, 2023)
This study explores the concept of positive communication culture as a unifying approach within organizations, aiming to strengthen human resource behaviors and business systems. Through an analytical descriptive approach, the study emphasizes the importance of this culture as an interactive communication pattern, an excellence criterion, and a defense system against crises. The results highlight the significance of an administrative pattern based on culture and behavior in achieving a positive communication culture. This culture, characterized by transparency, governance, and empowerment, acts as a barrier to safeguard the organization's gains.